Sustainable investing and public goods provision - Ilaria Piatti; Joel Andrew Shapiro; Xuan Wang (Queen Mary University of London, School of Economics and Finance, 2023)
We model investors that take into account the amount of public good that firms produce (e.g., by reducing carbon emissions) when making their portfolio allocation. In an equilibrium asset pricing model with production and public goods provision, we find that environmentally conscious investors invest more than others, invest more in clean firms, and may invest more in dirty firms. Whether clean firms exhibit CAPM alphas depends on the amount of systematic risk of the firm and its relative contribution to the public good. There is underprovision of the public good in equilibrium. Lower government provision may lead to a surge in investment and government provision may be dominated by green subsidies. Finally, we extend the model to analyze negative externalities, donations, and uncertainty regarding public good provision.
Keywords: G11; G12; H41; 330; Sustainable finance; ESG investing; public good provision; asset pricing